SISTEM INFORMASI PEMASARAN PRODUK JAJANAN LOMBOK BERBASIS E-COMMERCE - Muhammad Fahrurrozi; Yulistian Hidayaty; Muhammad Azmi; Yudi Sutaryana; Fitriani Fitriani; Khairunnazri Khairunnazri (TEKNIMEDIA: Teknologi Informasi dan Multimedia, 2025)
Ombak Food is one of the micro, small and medium enterprises (UMKM) that is used as a reference source, and a research place used to build an E-Commerce-based Marketing Information System Application. Ombak Food is an MSME that was established in 2017. Ombak Food originally came from the Sustainable Food House Area (KRPL) program in Bonjeruk Village, Jonggat District, Central Lombok Regency, West Nusa Tenggara (NTB). The Marketing Process running at Ombak Food still uses social media in the form of Instagram, Facebook, and Whatsapp, which is felt to be less than optimal in promoting products, accompanied by minimal access to information about new products owned for consumers to access, and recording incoming orders, is still done manually so that there is a lot of documentation of ordering goods that are input incorrectly and written repeatedly. One alternative that can be done to simplify the marketing and sales process is to use a website-based e-commerce information system that can facilitate Ombak Food in marketing products and the Sales Process Effectively. From the results of using the e-commerce-based information system application, the owner of Ombak Food felt a significant change in the sales process carried out, marked by an increase in the number of purchases made by consumers. The marketing process for new products produced is also easier to market.